Strategic Competencies In The Aspect Of Military Training - Rakhmatullaev Umid Karabaevich (Academia One Publishing, 2025)
Strategic competencies in military training are critical to prepare leaders who are able to effectively manage complex operations and interact with national and international structures. These competencies include a wide range of skills, from strategic thinking to interpersonal interactions, and are developed through a combination of formal education, professional training, and practical experience
Keywords: competence; strategy